Comparative Epigenomics Reveals Host Diversity of the Trichinella Epigenomes and Their Effects on Differential Parasitism - Feng, Yayan; Liu, Xiaolei; Liu, Yuqi; Tang, Bin; Bai, Xue; Li, Chen; Wang, Xuelin; Deng, Yiqun; Gao, Fei; Liu, Mingyuan (Frontiers in Cell and Developmental Biology, 2021)
Comparative epigenomics provides new insights on evolutionary biology in relation with complex interactions between species and their environments. In the present study, we focus on deciphering the conservation and divergence of DNA methylomes during Trichinella evolution. Whole-genome bisulfite sequencing and RNA-seq were performed on the two clades of Trichinella species, in addition to whole-genome sequencing. We demonstrate that methylation patterns of sing-copy orthologous genes (SCOs) of the twelve Trichinella species are host-related and can mirror known phylogenetic relationships. Among these SCOs, we identify a panel of genes exhibiting hyper-/hypo-methylated features in gene-bodies or respective promoters that play pivotal roles in transcriptome regulation. These hyper-/hypo-methylated SCOs are also of functional significance across developmental stages, as they are highly enriched species-specific and stage-specific expressed genes both in Ad and ML stages. We further identify a set of parasitism-related functional genes that exhibit host-related differential methylation and expression among those SCOs, including p53-like transcription factor and Cdc37 that are of functional significance for elucidating differential parasitology between the two clades of Trichinella. This comparative epigenome study can help to decipher the environmental effects on differential adaptation and parasitism of the genus Trichinella.